(untitled) - LeRoy Ladurie, Emmanuel (New York, 1979)
Tells ud about Montaillou, which has received even more praise than LeRoy Ladurie's earlier work, provides a portrait of a fascinating place with a dark, intriguing history
Keywords: Vùng Montaillou (Pháp),Montaillou (France),Montaillou (France),Vùng Montaillou (Pháp),Vùng Montaillou (Pháp),Vùng Montaillou (Pháp); Social life and customs,History,Religious life and customs,Đời sống tôn giáo và phong tục,Lịch sử,Đời sống xã hội và phong tục